Analisis Perlakuan Akuntansi Pajak Penghasilan atas Pemberian Fringe Benefits terhadap Laporan Keuangan setelah Berlakunya Undang-Undang Harmonisasi Peraturan Perpajakan - Muhammad Syapari; Arief Rahman (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
One of the most interesting points in the Harmonization of Tax Regulations Law (UU HPP) is the allowance for the deduction of fringe benefit expenses incurred by employers for tax purposes. Additionally, employees who receive fringe benefits are now subject to income tax, and these benefits can be included in their gross income for the calculation of Article 21 Income Tax. This provision contradicts the previous Income Tax Law, which did not classify in-kind benefits or perks as taxable income for employees. This research aims to understand respondents' understanding of the treatment of fringe benefit expenses under the UU HPP and how tax planning can be implemented to minimize taxable income. A qualitative descriptive approach, using observational methods such as interviews and case studies, will be employed. The research findings are expected to provide input for companies in implementing tax planning for fringe benefits.